INHIBITION EFFECTS OF CYCLOHEXANESPIRO-5-HYDANTOIN AND 1-AMINOCYCLOHEXANECARBOXYLIC ACID TOWARDS SOUR CHERRY POLLEN - Ganchev, Donyo; Marinov, Marin; Nikolov, Angel; Krustev, Stefan; Zlateva, Milena; Atanasova, Nadezhda; Stoyanov, Neyko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Possible deleterious effects of cyclohexanespiro-5-hydantoin and 1-aminocyclohexanecarboxylic acid to sour cherry pollen were examined with the current study. Dose-response odeling was carried out by R language for Statistical Computing, drc package.